Ensino de argumentação em projetos de letramento - Fernandes, Francisca Vaneíse Andrade (2021)
Argumentation is a fundamental competence for citizens to defend points of view, fight for rights, modify preexisting situations and statutes, being necessary for the strengthening of democracy. In this sense, thinking about the teaching of argumentation that presupposes this experience means focusing on social practice and the development of critical thinking. In order to contribute to this reflection, this thesis has the general objective of investigating the configuration of the argumentation teaching-learning process in literacy projects. Therefore, we outline some specific objectives: (i) to analyze argumentation as a social practice, experienced in the literacy projects developed; (ii) identify skills related to the competency of argumentation mobilized in these projects; (iii) to map the principles of teaching argumentation within the developed literacy projects. In order to achieve our goals, this research-action, with a qualitative approach and an ethnographic approach, takes an interpretative perspective, is anchored in Applied Linguistics and is based on literacy studies from a sociocultural perspective and on argumentation with an interactional basis. The investigation participants are 3rd-grade high school students from a public school in the state of Rio Grande do Norte and, in the process, we had the collaboration of teachers, principals, coordinators and school employees, in addition to agents outside the school environment: professionals from the State Department of Education and Culture (Secretaria Estadual de Educação e Cultura / SEEC-RN) and a researcher from the Letramentos e Contemporaneidade group. The instruments used for data generation were: participant observation, field notes, audio/video recordings, photographs, semi-structured questionnaires. From the data analysis, the following principles emerged: activities/genres network; argumentation/argumentativeness; construction of the counterword; mobilization of skills/competencies. The results highlight that the teaching of argumentation through literacy projects enables the experience of argumentation as a social practice.